CLIMATE CHANGE VULNERABILITIES and RESPONSES IN A DEVELOPING COUNTRY CITY : LESSONS FROM COCHIN, INDIA - Thomas J. Wilbanks, J. Timothy Ensminger, and C. K. Rajan (ENVIRONMENT VOLUME 49 NUMBER 2007, 2007)
Many aspects of sustainability are focused on where people live, and increasingly worldwide, people live in cities.1 Looking a half-century or more into the future, one of the key issues for the world's cities is coping with rapid growth,2 especially when cities are in locations vulnerable to environmental stress, and a very salient example of an emerging environmental stress is climate change.3 How might a city-especially in the developing world-be vulnerable to impacts of climate change, and what kinds of responses make sense for them now in a larger context of sustainable development? Consider the case of Cochin, India.